Justice-Involved Veterans & Social Work: A Resource Dependence Theory Perspective - Schaffer, Bradley (International Journal of Criminology and Sociology, 2022)
The salience of justice-involved military veterans endures as a pervasive social problem in the United States of America (USA). Since the 1980’s the percentages of Justice-Involved Veterans (JIV) have varied from a reduction in Vietnam to increasing numbers of Global War on Terror (GWOT) veterans (Bureau of Justice Statistics Report, 2015). In response, there has been a proliferation of magistrate diversion, correctional specialty units, Veterans Treatment Courts (VTC) and programming for JIV. Much of the progress is due to concerted identification and organizational sharing of resources. The USA Department of Veterans Affairs (VA), courts, corrections and non-profit organizations (NPO) provide a valuable service to our military men and women to remediate the JIV needs. Social work plays at critical in practice areas at the penal, VA and NPO systems in the USA. The JIV population are examined through the lens of social work practice, resource dependence theory (RDT), case example and future direction. The examination highlights the importance of internal and external resources and partnerships to meet organizational goals and to remediate JIV psycho-social problems.